FUNGSI TARI JEPIN MELAYU SAYAN DI MASYARAKAT DUSUN MUARA COMAT KABUPATEN MELAWI - Vawaka, Dinda Elsa; Istiandini, Winda; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated to explore the function and development of Jepin Melayu Sayan dance it is based on the growing era, Jepin Melayu Sayan dance is increasingly rarely displayed. Whereas a traditional dance has a role in the life of the community and a characteristic of a society, especially the Malay tribe.Based on the data analysis, it is concluded that Jepin Melayu Sayan dance has a social function at harvest event which is displayed as a form of gratitude to Allah Swt for the harvested product. Function of entertainment for some residents who help the wedding preparation and entertainment for invited guests at weddings. The music used Gong, Ketawa’ and Gambus as music instrument and Syair Dialek Melayu Melawi song. The make up and the costum used was malay custom with natural make up. The show place used can be at proscenium and arena stage. The result research can be used to be a teaching material in art and culture on 10th grader. Keywords: Dance Function, JepinMelayuSayan dance, Melawi District